Influence of boundary conditions on the Southern Hemisphere atmospheric circulation during the last glacial maximum - Justino, F.; Souza, E.; Amorim, M. C.; Dias, P. L. Silva; Lemos, C. F. (Revista Brasileira de Meteorologia, 2008)
Based upon coupled climate simulations driven by present day and glacial boundary conditions, we demonstrate that although the ice sheet topography modifications during the glacial period are primarily placed in the Northern Hemisphere (NH), a climate simulation that employs the ICE-5G glacial topography delivers significantly enhanced climate anomalies in the Southern Hemisphere (SH) as well. These conditions, in association with climate anomalies produced by the modification of the atmospheric CO2 concentration characteristic of the Last Glacial Maximum (LGM) interval, are shown to be the primary forcing of the SH climate during this epoch. Climate anomalies up to -6°C over the Antarctic region and -4°C over South America are predicted to occur in respect to present day conditions. Accompanying the SH cooling in the LGM simulation there exists a remarkable reduction in the specific humidity, which in turn enforces the overall Southern Hemisphere cooling due to the weaker greenhouse capacity of the dry atmosphere.

Com base em simulações numéricas conduzidas com condições de fronteiras características dos períodos glaciais e atual, demonstra-se que embora as maiores anomalias da topografia da Terra no período glacial estejam no Hemisfério Norte, esta inclusão dos blocos de gelo leva a substanciais mudanças na circulação atmosférica austral para aquela época, indicando uma forte teleconexão inter-hemisférica. Em associação com a redução nos níveis de carbono atmosférico para 200 ppm, anomalias de temperatura de -6°C em torno da região antártica, e -4°C no continente sul-americano são simuladas para o último máximo glacial (UMG) em relação a condições atuais. Concomitantemente, o UMG é caracterizado por uma drástica redução na umidade específica, que por sua vez intensifica o esfriamento inicial devido à mais fraca capacidade de estufa da atmosfera mais seca.
Keywords: Last glacial maximum; Climate changes; Baroclinic activity; Último máximo glacial; Mudanças climáticas; Baroclinia; CO 2